Methylome changes in Lolium perenne associated with long-term colonisation by the endophytic fungus Epichloë sp. LpTG-3 strain AR37 - Forte, Flavia Pilar; Malinowska, Marta; Nagy, Istvan; Schmid, Jan; Dijkwel, Paul; Hume, David E.; Johnson, Richard D.; Simpson, Wayne R.; Asp, Torben (Frontiers in Plant Science, 2023)
Epichloë spp. often form mutualistic interactions with cool-season grasses, such as Lolium perenne. However, the molecular mechanisms underlying this interaction remain poorly understood. In this study, we employed reduced representation bisulfite sequencing method (epiGBS) to investigate the impact of the Epichloë sp. LpTG-3 strain AR37 on the methylome of L. perenne across multiple grass generations and under drought stress conditions. Our results showed that the presence of the endophyte leads to a decrease in DNA methylation across genomic features, with differentially methylated regions primarily located in intergenic regions and CHH contexts. The presence of the endophyte was consistently associated with hypomethylation in plants across generations. This research sheds new light on the molecular mechanisms governing the mutualistic interaction between Epichloë sp. LpTG-3 strain AR37 and L. perenne. It underscores the role of methylation changes associated with endophyte infection and suggests that the observed global DNA hypomethylation in L. perenne may be influenced by factors such as the duration of the endophyte-plant association and the accumulation of genetic and epigenetic changes over time.